Transplant/organ donation and transgender / Ahmad Husaini Abd Karim … [et al.] - Abd Karim, Ahmad Husaini; Muhamad Shaifuddin Shah, Muhammad 'Amirul Hazim; Azizi, Muhammad Hakim; Sh Abdul Halim, Sh Mohd Ashaari (2023)
In today's world. there are many issues of transplant, organ donation and transgender. Islam offers a deep and complex viewpoint on a wide range of topics, such as gender identity, organ transplants, and medical advancements. Islam typically supports organ transplantation as long as it is carried out ethically and meets a legitimate medical need. Most Islamic scholars concur that saving a human life is more important than many other factors. Organ transplants are frequently justified by the "Maqasid al-Shariah" (preservation of life) concept, provided that the organs are procured and transplanted via morally and legally acceptable methods. Numerous fatwas, or religious decrees, promoting organ donation have been issued by Islamic scholars and organisations.